THE CORRELATION BETWEEN SELF-CONFIDENCE AND MATHEMATIC LEARNING OUTCOMES FOR FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN KROYA SUB DISTRICT IN ACADEMIC YEAR OF 2020/2021 - Rifqi Roni Chasbulloh; Muhamad Chamdani; Ngatman Ngatman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed to examine positive correlation between self-confidence and mathematics learning outcomes for fifth grade students of public elementary schools in Kroya Sub District in academic year of 2020/2021 and to calculate the contribution of self-confidence on mathematics learning outcomes for fifth grade students of public elementary schools in Kroya Sub District in academic year of 2020/2021. The research was quantitative correlational study. The results indicated that self-confidence had positive correlation on mathematics learning outcomes (Sig. 0.000 <0.05) and correlation coefficient was 0.504. It indicated strong correlation based the interpretation of de vaus correlation coeffiicient ranged from 0,50 to 0,69. Self-confidence contributed 25.34% on mathematics learning outcomes and the remaining 74.66% was influenced by other factors such as learning interest, learning readiness, intelligence, etc. It meant that the higher self-confidence, the higher students' mathematics learning outcomes.